2016
DOI: 10.1186/s12955-016-0532-5
|View full text |Cite
|
Sign up to set email alerts
|

Where’s WALY? : A proof of concept study of the ‘wellbeing adjusted life year’ using secondary analysis of cross-sectional survey data

Abstract: BackgroundThe Quality-Adjusted Life Year (QALY) is a measure that combines life extension and health improvement in a single score, reflecting preferences around different types of health gain. It can therefore be used to inform decision-making around allocation of health care resources to mutually exclusive options that would produce qualitatively different health benefits. A number of quality-of-life instruments can be used to calculate QALYs. The EQ-5D is one of the most commonly used, and is the preferred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…There is no consensus on how to measure the effectiveness of charities that address other causes, such as the arts, education, or homelessness. Some propose generalizing QALYs by replacing them with well-being-years (WELLBYs) [99,111]. The WELLBY measure aims to incorporate all aspects of well-being, not just health outcomes.…”
Section: Innumeracymentioning
confidence: 99%
“…There is no consensus on how to measure the effectiveness of charities that address other causes, such as the arts, education, or homelessness. Some propose generalizing QALYs by replacing them with well-being-years (WELLBYs) [99,111]. The WELLBY measure aims to incorporate all aspects of well-being, not just health outcomes.…”
Section: Innumeracymentioning
confidence: 99%
“…A later definitive trial may extract key resource use items from the Mental Health The feasibility trial identified limitations in expressing the cost-effectiveness of the E-PAtS programme in terms of incremental cost per unit change in the WEMWBS proposed primary outcome measure. The WEMWBS is not currently a preference-based measure that permits the estimation of quality-adjusted life years (QALYs) amenable to cost-effectiveness decision-making (42). |The feasibility trial identified a number of attributes from the qualitative research that can potentially be incorporated into a discrete choice experiment (DCE), a preference-based approach for valuing potentially disparate effects of interventions.…”
Section: Participant-reported Outcome Measuresmentioning
confidence: 99%
“…Aims A mixed-method process evaluation was integrated into the outcome and economic evaluations, 79 following a 'nested' design. 80 The primary aim of the process evaluation was to support the interpretation of the outcome data and further refine the programme theory.…”
Section: Process Evaluationmentioning
confidence: 99%